Simulating Rainwater Harvesting System Performance for a Campus University in Malaysia - Wong, Chuan Yuen; Teo, Fang Yenn; Goh, Boon Hoe; Mah, Yau Seng (Emerald Publishing, 2021)
This study provides a performance analysis of using a rainwater harvesting system (RWHS) to supply water for toilet flushing and garden watering, with reference to a student accommodation hall in the University of Nottingham Malaysia in Semenyih, Selangor, Malaysia. Three different models were used in this analysis, in which the monthly analysis was based on the mass-balance approach, while the daily analysis was based on the yield before spillage and yield after spillage algorithms to define the tank release rule based on different sizes of storage tank (i.e. 3, 5, 7 and 10 m3). The performances of the various storage tanks were presented for water saving and reliability. The monthly analysis found promising results of collectable water on the demand, in which the average reliability is higher than 50%. Also, the daily water balance simulation verified the results from the monthly analysis. A cost analysis was performed that the best storage rainwater harvesting tank size was 10 m3 for the combined demand of toilet flushing and garden watering. Based on the findings, the proposed implementation of RWHS in the chosen campus university was reliable, not only environmentally beneficial but also economically viable.